Estrés laboral y su incidencia en la productividad pericial en la policía nacional, distrito Manta - Ponce-Basurto, Juan Alejandro; Palma-Macías, Gregorio Rigoberto (MQRInvestigar, 2025)
The work, social and cultural activities of contemporary society in which human beings are immersed are having a negative impact on their health and it is precisely stress. The present study was developed with the objective of analyzing the incidence of work stress on the expert productivity of the National Police, Manta District. Questionnaires were applied using the Google Form program: to analyze the incidence of work stress and to diagnose the current state of expert productivity in the National Police, Manta district. The SPSS version 25 program was applied. The selected sample was 17 police officers from the district of Manta, with a Spearman correlation coefficient of .111, which showed that there is a systematic relationship between work stress and expert productivity: interpreting that the Work stress has a notable, but not definitive, impact on expert productivity. It is concluded that there is a correlation that indicates that, although stress can affect the performance of experts, it does not always have a negative impact. In fact, a little stress can even help them focus and work more efficiently. However, it is essential that the National Police, Manta district strive to promote a healthier work environment that minimizes its effects on the activities of the servants in charge of preparing the corresponding expert reports, which would impact their work productivity.